ANALISIS PENGARUH FAKTOR PSIKOLOGIS, SOSIAL, DAN SITUASIONAL TERHADAP CARA PANDANG KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN DI PASAR TRADISIONAL Ir. SOEKARNO SUKOHARJO - Erni Widiastuti (Universitas Slamet Riyadi, 2020)
The purpose of this study was to determine and measure the influence of psychological factors, social factors, and situational factors, both partially and simultaneously on the consumer's perspective in making purchasing decisions in the traditional market, Ir. Soekarno Sukoharjo. The hypotheses in this study are: It is suspected that psychological factors, social factors, and situational factors have a significant effect both partially and simultaneously on the perspective of consumers in making purchasing decisions in traditional markets .Ir. Soekarno Sukoharjo. The data needed in this study are primary data obtained by the questionnaire method from a sample of 100 respondents. Analysis of the data used in this study is a multiple linear regression test, t test, F test and the coefficient of determination test. The results of data analysis in this study can be concluded that psychological factors, social factors, and situational factors have a significant positive effect both partially and simultaneously on the consumer's perspective in making purchasing decisions in traditional markets. Ir. Soekarno Sukoharjo. Judging from the magnitude of the coefficient of determination (adjusted R square) which has a positive value of 0,843, shows that the consumer's perspective in making purchasing decisions in traditional markets Ir. Soekarno Sukoharjo explained by psychological factors, social factors, and situational factors of 84,3% and the remaining 15,7% illustrates the existence of other free variations not observed in this study.